2014
DOI: 10.1016/j.jneumeth.2013.11.018
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of visual sampling during real-world activity in Parkinson's disease and healthy controls: A structured literature review

Abstract: Future research is required to accurately characterise visual impairments in Parkinson's disease and during real-world activities. Composite use of instruments may be required to achieve reliability and validity of visual sampling outcomes which need to be standardised. Recommendations also include assessment of cognition and basic visual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 85 publications
0
46
0
Order By: Relevance
“…Impaired visual function has been well described in Parkinson’s disease but its impact on movement is less clear [42-47]. The visual difficulties observed in this study are interesting for two reasons.…”
Section: Discussionmentioning
confidence: 75%
“…Impaired visual function has been well described in Parkinson’s disease but its impact on movement is less clear [42-47]. The visual difficulties observed in this study are interesting for two reasons.…”
Section: Discussionmentioning
confidence: 75%
“…Visual deficits have been suggested as a premotor marker for PD patients. Clinical observations and animal model studies have provided evidence that PD patients have color discrimination dysfunction (Bodis‐Wollner, ; Stuart et al, ), which may be a disease‐specific feature of PD (Piro et al, ). Visual deficits are a risk factor for developing visual hallucination (VH; Matsui et al, ).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Clinical observations and animal model studies provide evidence that visual dysfunction, in general, tends to manifest at an early stage in PD (Chaudhuri et al, ; Bodis‐Wollner, ). The visual processing extends from the retinal to the ventral temporal lobe, which is also modified by top‐down as well as bottom‐up processing (Willis, ; Stuart et al, ). Botha and Carr () reported that complex visual hallucinations can affect temporal lobe structures that are modulated by dopamine.…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
“…However, until recently almost all previous research was conducted in restricted static conditions and involved simple tasks such as button pressing [12]. These studies provide information about the mechanisms behind eye movement characteristics and allow for experimental manipulation, but results may not be relevant to real-world activities that involve multiple motor, cognitive and visual processes.…”
Section: B Focusmentioning
confidence: 99%
“…The Dikablis and EOG (sampling at 1000Hz) were synchronized using a 3D motion capture system (Vicon, Oxford, UK). Importantly for this study the 50Hz sampling rate of the Dikablis is adequate for the detection of saccades, although it may not be able to provide precise information on saccade durations or peak velocity as these features require higher sampling frequencies (>200Hz) [11][12][13].…”
Section: B Equipmentmentioning
confidence: 99%